To save the land and people : a history of opposition to surface coal mining in Appalachia - Montrie, Chad (University of North Carolina Press, 2003)
This text charts the people's movement to ban strip mining in Appalachia, tracing popular opposition to the industry from its inception through the growth of a militant movement engaging in acts of sabotage. It highlights the role of farmers and working people in this movement.